Lithium Ion Breathable Electrodes with 3D Hierarchical Architecture for Ultrastable and High‐Capacity Lithium Storage - Li, Ying‐Qi; Li, Jian‐Chen; Lang, Xing‐You; Wen, Zi; Zheng, Wei‐Tao; Jiang, Qing (Advanced functional materials, 2017)
Transition‐metal oxides show genuine potential in replacing state‐of‐the‐art carbonaceous anode materials in lithium‐ or sodium‐ion batteries because of their much higher theoretical capacity. However, they usually undergo massive volume change, which leads to numerous problems in both material and electrode levels, such as material pulverization, instable solid‐electrolyte interphase, and electrode failure. Here, it is demonstrated that lithium‐ion breathable hybrid electrodes with 3D architecture tackle all these problems, using a typical conversion‐type transition‐metal oxide, Fe3O4, of which nanoparticles are anchored onto 3D current collectors of Ni nanotube arrays (NTAs) and encapsulated by δ‐MnO2 layers (Ni/Fe3O4@MnO2). The δ‐MnO2 layers reversibly switch lithium insertion/extraction of internal Fe3O4 nanoparticles and protect them against pulverizing and detaching from NTA current collectors, securing exceptional integrity retention and efficient ion/electron transport. The Ni/Fe3O4@MnO2 electrodes exhibit superior cyclability and high‐capacity lithium storage (retaining ≈1450 mAh g−1, ≈96% of initial value at 1 C rate after 1000 cycles). 3D lithium‐ion breathable hybrid electrodes are successfully constructed by anchoring Fe3O4 nanoparticles onto highly conductive 3D current collectors of Ni nanotube arrays and encapsulating them with reversibly switching δ‐MnO2 layers. As a result of integrity retention and efficient ion/electron transport, the Ni/Fe3O4@MnO2 electrodes exhibit superior cyclability and high‐capacity lithium storage.